2023
DOI: 10.1039/d3sc04903e
|View full text |Cite
|
Sign up to set email alerts
|

Bioorthogonal dissociative rhenium(i) photosensitisers for controlled immunogenic cell death induction

Guang-Xi Xu,
Lawrence Cho-Cheung Lee,
Peter Kam-Keung Leung
et al.

Abstract: Photosensitisers for photoimmunotherapy with high spatiotemporal controllability are rare. In this work, we designed rhenium(I) polypyridine complexes modified with a tetrazine unit via a bioorthogonally activatable carbamate linker as bioorthogonally...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…1299 Lo and co-workers have utilized this "click-torelease" strategy to develop rhenium(I) tetrazine complexes (698) (Chart 315) as bioorthogonally activatable photosensitizers. 1300 These complexes display weak emission (Φ em = 0.029 to 0.039) and 1 O 2 photosensitization (Φ Δ = 0.22 to 0.48) due to the quenching tetrazine moiety. Incubation of the complexes with TCO induces the bioorthogonal cleavage reaction, increasing both the emission intensities and 1 O 2 generation efficiencies of the complexes.…”
Section: Inverse Electron-demand Diels−alder Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…1299 Lo and co-workers have utilized this "click-torelease" strategy to develop rhenium(I) tetrazine complexes (698) (Chart 315) as bioorthogonally activatable photosensitizers. 1300 These complexes display weak emission (Φ em = 0.029 to 0.039) and 1 O 2 photosensitization (Φ Δ = 0.22 to 0.48) due to the quenching tetrazine moiety. Incubation of the complexes with TCO induces the bioorthogonal cleavage reaction, increasing both the emission intensities and 1 O 2 generation efficiencies of the complexes.…”
Section: Inverse Electron-demand Diels−alder Reactionmentioning
confidence: 99%
“…One example is the IEDDA reaction between a methylene carbamate-substituted tetrazine and a TCO, which induces carbamate cleavage and liberates a secondary amine . Lo and co-workers have utilized this “click-to-release” strategy to develop rhenium(I) tetrazine complexes ( 698 ) (Chart ) as bioorthogonally activatable photosensitizers . These complexes display weak emission ( Φ em = 0.029 to 0.039) and 1 O 2 photosensitization ( Φ Δ = 0.22 to 0.48) due to the quenching tetrazine moiety.…”
Section: Luminescent Transition Metal Complexes As Bioorthogonal Probesmentioning
confidence: 99%
“…Photodynamic therapy (PDT) is a promising therapeutic strategy to circumvent these defects. As a light-driven modality, with the high spatiotemporal selectivity of light, reactive species can be generated explicitly in cancer locations and thus avoid noncancerous tissue damage. Traditionally, PDT-inducing cell death was categorized into apoptosis or uncontrolled necrosis . However, current observations revealed that cancer cells can pass through various nonconventional cell death pathways after PDT processes. , Liu designed membrane anchoring photosensitizers with aggregation-induced emission characteristics for cancer cell ablation via photoactivated pyroptosis .…”
Section: Introductionmentioning
confidence: 99%